Assuming the missing signs are pluses, that factors to (4y + 1)(y + 6)
Chat with our AI personalities
4y2 + 25y + 6
To factor 4y^2 + 25y + 6, you can split the middle term by finding two numbers whose product is equal to 4 * 6 (the product of the first and last terms) and whose sum is equal to the coefficient of the middle term, which is 25. In this case, the numbers are 4 and 1. So, you can rewrite the expression as (4y + 1)(y + 6).
In the equation x = 4y2 + 6 where x = 42, we need to substitute 42 for x and solve for y. x = 4y2 + 6 42 = 4y2 + 6 42 - 6 = 4y2 + 6 - 6 36 = 4y2 36 / 2 = 4y2 / 2 18 = 4y 18 / 4 = 4y / 4 9 / 2 = y 4 1/2 = y (or 4.5 = y)
(3 - 2y)(3 + 2y)
If you're looking to factor this expression, then you need to find two values that add up -20, and which multiply to make 4. Unfortunately, no such terms exist, so this expression can not be factored.